Effect of annealing treatment on luminescence property of MgO nanowires - Thanut Jintakosol (2018)
Magnesium oxide nanowires (NWs) were synthesized by a current heating process. The effect of annealing treatment in air on their structural and optical characteristics was investigated. As-grown NWs in diameter ranging from 30 to 70 nm and length up to several 10 μm were obtained. Carbon-coating layers were observed in the as-grown NWs which were oxidized during the annealing treatment at high temperature. Ionoluminescence spectra of the as-grown and annealed NWs have showed two emission peaks centered at 360 nm (UV emission) and 492 nm (green emission). The intensities of green emission were maximum at the annealing temperature of 650 °C for 2 h, whereas those of UV emission were decreased with increasing the annealing temperature. It is anticipated that maximum green emission correlates to the sufficient density of oxygen vacancies which was occurred by the optimum annealing parameters of both temperature and time. © 2009 Elsevier B.V. All rights reserved.